Causes And Problems Of Population Displacement Of The Mishings Of Dhemaji Due To Flood Vulnerability (International Journal of Scientific Research and Management (IJSRM), 2015)
The Government has identified Dhemaji district as the most backward and poorest district in the State, mainly due to the fact that most portion of the area is affected by yearly floods. The population inhabited by different people groups such as Mishing, Bodos, Deories, Assamese, Adivasi, Muslim and various non tribal groups. The total current population of Dhemaji is 688077.The male & female population showcasing 353043 and 335034 respectively. The Mishing community constitutes the largest population of the area. The Mishing people are active agriculturists. Their main occupation for livelihood is agriculture. In the past, they had a practice of shifting cultivation in the hills but after settling down in the plains, they are now practicing settled cultivation. The literacy rate of the Mishing people is poor. The State literacy rate has gone up to 73% percent whereas the Mising literacy rate is at 45% in the district. This is due to a lack of proper educational institutions, a lack of awareness and also due to the yearly flood disaster in the district. Education has been given very little priority. The health status of the people is very poor. Water-borne diseases in the area are rampant due to floods and stagnant water after the disasters. The yearly flood have been destroying their cultivable land by soil erosion or by sand deposition, damaging educational institutions, washing away their properties that is private property as well as public property and even sometimes taking away peoples life. The frequent flood disasters in the area have been increasing the percentage of BPL card holders yearly. Aftermath of flood disaster this particular tribe lack rehabilitation tribulations due to various factors. It has been observed that their simple way of settlement pattern has been affected by flood resulting displacement of households to elsewhere. In the recent year we have been seen that a new trend of settlement pattern that is settlement in the broken embankments or high platforms or highland areas. Therefore, in order to analysis the actual facts within the districts a case study were conducted in the Machakhowa Dev. Block and Sissiborgaon Dev. Block. The research paper is entitled as “Causes and Problems of Population Displacement of the Mishings of Dhemaji due to Impact of Flood Vulnerability”.